2014
DOI: 10.1155/2014/267189
|View full text |Cite
|
Sign up to set email alerts
|

High Potential Source for Biomass Degradation Enzyme Discovery and Environmental Aspects Revealed through Metagenomics of Indian Buffalo Rumen

Abstract: The complex microbiomes of the rumen functions as an effective system for plant cell wall degradation, and biomass utilization provide genetic resource for degrading microbial enzymes that could be used in the production of biofuel. Therefore the buffalo rumen microbiota was surveyed using shot gun sequencing. This metagenomic sequencing generated 3.9 GB of sequences and data were assembled into 137270 contiguous sequences (contigs). We identified potential 2614 contigs encoding biomass degrading enzymes inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 44 publications
4
19
0
Order By: Relevance
“…In this study, the most highly represented GH family was GH2 (which comprises β-Dgalactosidase, β-glucuronidase, β-D-mannosidase, and exo-β-glucosaminidase [38]) followed by the GH43 (which includes β-xylosidase, β-1,3-xylosidase, α-L-arabinofuranosidase, arabinanase, xylanase, galactan 1, and 3-β-galactosidase). Our results are in accordance with the finding that GH3 and GH2 are the predominant GHs in the rumen of Indian buffalo [3,35,36]. GTs catalyze the binding of sugars to glycosyl groups; we found that GT2, GT4, GT27, GT5, and GT41 families were the most highly represented in the rumen of cattle-yaks.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, the most highly represented GH family was GH2 (which comprises β-Dgalactosidase, β-glucuronidase, β-D-mannosidase, and exo-β-glucosaminidase [38]) followed by the GH43 (which includes β-xylosidase, β-1,3-xylosidase, α-L-arabinofuranosidase, arabinanase, xylanase, galactan 1, and 3-β-galactosidase). Our results are in accordance with the finding that GH3 and GH2 are the predominant GHs in the rumen of Indian buffalo [3,35,36]. GTs catalyze the binding of sugars to glycosyl groups; we found that GT2, GT4, GT27, GT5, and GT41 families were the most highly represented in the rumen of cattle-yaks.…”
Section: Discussionsupporting
confidence: 92%
“…To date, 42 unique strains of cellulase-and GH-producing bacteria have been identified [36]. GHs hydrolyze glycosidic [3]. Most of the GHs identified in our study were oligosaccharide-degrading enzymes such as cellulase, hemicellulose, and pectinase that degrade the plant cell wall to produce oligosaccharides [37].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…To analyze microbial diversity, 16S rRNA amplicon-based sequencing has been widely used in various engineered or environmental samples (Hess et al, 2011;Singh et al, 2014;Chan et al, 2015;Mhuantong, Charoensawan, Kanokratana, Tangphatsornruang, & Champreda, 2015;Vishnivetskaya et al, 2015). Culture independent studies at hot springs in YNP have a long research history where the clonal library was initially used (Brock, 1967;Thiel et al, 2016).…”
Section: Microbial Diversity Analysis In Sk-ymentioning
confidence: 99%
“…The intestinal microbiota of various animals, which can degrade complicated carbohydrates, is under investigation as a resource for the discovery of novel enzymes for e.g. more efficient breakdown of organic waste streams and non-food biomass for the production of biofuel [40,41]. The intestines of elephants [42], koalas [43], and termites [44] harbour microbes with a totally different capacity for polysaccharide and lignin breakdown, which could be utilized in such processes.…”
Section: What Is Being Sequenced and Which Questions Can This Answer?mentioning
confidence: 99%